IRF4 suppresses osteogenic differentiation of BM-MSCs by transcriptionally activating miR-636/DOCK9 axis (Clinics, 2022)
Objectives: Osteoblasts are derived from Bone Marrow-derived Mesenchymal Stem Cells (BM-MSCs), which play an indispensable role in bone formation. In this study, the authors aim to investigate the role of IRF4 in the osteogenic differentiation of BM-MSCs and its potential molecular mechanism.Methods: The authors used lentivirus infection to overexpress IRF4 in BM-MSCs. The expression of IRF4 and osteogenesis-related genes were detected by qRT-PCR and western blot analysis. The osteogenic differentiation of BM-MSCs was evaluated by Alkaline Phosphatase (ALP) activity, Alizarin red staining, and Alkaline Phosphatase (ALP) staining. Chromatin Immunoprecipitation (ChIP), Dual-Luciferase reporter assay and RNA Immunoprecipitation Assay were applied to confirm the regulatory mechanism between IRF4, miR-636 and DOCK9.Results: The authors found IRF4 was down-regulated during the osteogenic differentiation of BM-MSCs, and IRF4 overexpression could decrease the osteogenic differentiation of BM-MSCs by specifically promoting the reduction of Alkaline Phosphatase (ALP) activity and down-regulating osteogenic indicators, including OCN, OPN, Runx2 and CollA1. Mechanistically, IRF4 activated microRNA-636 (miR-636) expression via binding to its promoter region, and Dedicator of Cytokinesis 9 (DOCK9) was identified as the target of miR-636 in BM-MSCs. Moreover, the damage in the capacity of osteogenic differentiation of BM-MSCs induced by IRF4 overexpression could be rescued by miR-636 inhibition.Conclusions: In summary, this paper proposed that IRF4/miR-636/DOCK9 may be considered as targets for the treatment of osteoporosis (OP).